CORROSION INHIBITION OF ZINC IN HYDROCHLORIC ACID MEDIUM BY THIOUREA AND GUANIDIN. - Al-Saadie, Khulood (Iraqi Journal of Science, 2024)
The inhibition action of thiourea and guanidine on the corrosion behavior of zinc in 1M HCl was investigated using weight loss measurement and by following the zinc ions concentration in solution after several times by atomic absorption spectroscopy (AAS). The two inhibitors reduced the corrosion rate of zinc and the protection efficiency ranging between(10.6-59.8) at low temperature (285, 299) K and the two inhibitors get to a similar protection at (318, 328) K almost. Adsorption isotherm was like the Langmuir adsorption isotherm. The two organic compounds reduced the rate of the hydrogen evolution reaction.